The Temporality of Crisis and the Crisis of Temporality: On the Construction and Modulation of Urgency During Prolonged Crises - Skade, Lorenzo; Lehrer, Elisa; Hamdali, Yanis; Koch, Jochen (Journal of management studies, 2025)
Despite the increasing frequency and awareness of large‐scale crises, our knowledge of how organizations construct urgency to act in these extreme contexts – especially if they are prolonged disasters rather than single events – remains limited. By undertaking an explorative study of the Robert Koch Institute (RKI), the central German organization for disease control and prevention during the COVID‐19 pandemic, we address the research question of how organizations construct urgency during prolonged crises. In doing so, we develop a process model of the construction and modulation of urgency. Specifically, we draw on a temporal perspective to argue that the RKI translated temporal cues of the crisis to mobilize different forms of urgency via the central mechanism of modulating urgency (i.e., by speeding up or slowing down activities) over an extended period of time. Our findings contribute to an advanced understanding of the role of temporality and urgency during prolonged crises by (1) showing how urgency is enacted through temporal practices, (2) extending the literature on temporality and how organizations materialize temporality to construct and modulate urgency, and (3) demonstrating that various forms of urgency exist, rendering it a much more multifaceted concept than previously suggested.